The financial management practices of selected food establishments in the university belt Manila: Basis for a financial literacy framework of small businesses - Eleuterio, John Gabriel P., Fraga, Ana Victoria S., Jimenez, Mariz Sophia M., Maure, Raymond Louise L., Mendoza, Realyn Ann S., Sandigan, Hidei M., Tablada, Crystelle D. 4 0 16; 5 (2024)
Abstract One of the contributors to economic growth are small food establishments as they are convenient and offer quick service, food service outlets have become the go- to option for Filipino customers looking to eat out or buy food. Even though these businesses make a substantial contribution to the local economy, little is known about the precise financial management techniques that make them successful. According to a study, financial management techniques and SMEs' profitability are positively correlated. Additionally, it has been proposed that comprehension of the entire performance of small and medium-sized businesses (SMEs) is greatly aided by financial literacy. Still, very little is known about its influence, and the scant research that is available is dispersed. Thus, the research conducted a personal administered survey among 41 business owners or managers located in the University belt, Manila; the survey was formulated on the statement of the problems that are about the knowledge of literacy of food establishments on the financial management practices and utilized a five-point Likert scale to gauge their responses. The results of the study conveyed that there is a strong understanding of the importance and significance of the financial management practices towards the business. The respondents observed simple practices of bookkeeping and recording of fiscal transactions but did not comply with complex practices like the analyzation and formulation of strategies in regard to forecasting, financial statement analysis, and so on. There is also a gap of information on the loans and grants that the government offers and a mixed opinion on how cash flow is handled that relates to their concern of handling financial statements. Majority of these business owners rely on guesswork for their financial decision which emphasizes the ends for structured financial literacy training to develop their management skills. The study recommends a formulation of a literacy framework of small business conforming financial management practices; this tool could be utilized and employed by government bodies that concern the business sector of a locale, researchers, and business owners alike. The formulated framework encompasses a systemic learning of the financial knowledge, practices, and business confidence with the specific actions to monitor and develop a more enhanced financial literacy.
Business Research: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2